Peran Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan Dalam Optimalisasi Pendapatan Asli Daerah Di Kabupaten Trenggalek - Hanifa Aqil; Kennes Novisyadhenti; Wahyu Sultan Maulana; Wicaksono, Galih (PT. Banjarese Pacific Indonesia, 2024)
Rural and Urban Land and Building Tax or what can be called PBB-P2 is one of the revenues included in Regional Original Income (PAD). With the existence of Law Number 23 of 2014 which is an amendment to Law Number 32 of 2004 concerning Regional Government, and Law Number 33 of 2004 concerning Financial Balance between the Central Government and Regional Government which will give authority to the Government Regions to PBB-P2 areas in order to carry out government functions and increase regional income sources. The research method used is descriptive quantitative using several data obtained from research conducted by the Central Statistics Agency from 2017 to 2021. Based on the results of this research, it shows that the level of PBB-P2 effectiveness in Trenggalek Regency is classified as very effective. In contrast to the level of contribution of Rural and Urban Land and Building Tax to PAD, it is actually still not optimal. With this research, it is hoped that Trenggalek Regency can create new strategies and treatments to improve the system for managing Rural and Urban Land and Building Tax revenues in the context of optimizing Original Regional Income in Trenggalek Regency.